Factors Associated with Utilisation of Post natal Care Services in Lwengo Sub- County, Lwengo District, Uganda: A Cross Sectional Study. - Nakityo , Constasio; Laban, Waswa Bright; Atukunda, Gershom (Student's Journal of Health Research Africa, 2025)
Introduction: Postnatal care is the support provided to mothers and their newborns from the time of birth up to six weeks afterward. This period is crucial because many mothers and babies die during these weeks. Despite being a vital part of mothers' and children's health, postnatal care (PNC) continues to be one of the most neglected aspects of reproductive health programs. Objective: The main objective of the study was to examine the factors associated with utilization of post-natal care services from 2002 to 2025 in Lwengo sub-county, Lwengo District. Methods: The study was conducted in Lwengo Sub–County. A total of 370 mothers participated in this research. Quantitative data were gathered through questionnaires with 250 mothers, while qualitative data were obtained via semi-structured interviews and focus group discussions with 120 mothers and healthcare workers, using Simple Random Sampling. Quantitative data was analysed by logistic regression, and qualitative data by content from descriptions by participants. Results: Mothers who did not know the PNC services they were supposed to receive after birth were 59% less likely to attend compared to mothers who know the services offered after delivery. Mothers who had no check-ups at a health facility while pregnant were 65% less likely to attend the PNC services compared to those who had check-ups during pregnancy. The qualitative analysis of interviews reported the major obstacles to uptake for the PNC services by mothers from the key informant interviews included la ack of knowledge about PNC services, a lack of designated rooms purposely for postnatal services, behaviour of some midwives towards the mothers. Conclusion: 57.6% of participants used PNC services. Key determinants included awareness of PNC, proximity to health facilities, and facility readiness. Recommendations: Deploying more midwives, improving facility infrastructure, and enhancing community education on PNC by the Government of Uganda.